Muzyka jako środek narracji w wybranych filmach Michaela Hanekego - Woźniak, Maciej (Załącznik Kulturoznawczy, 2023)
The author of the article analyzes the narrative role of music in Michael Haneke’s films. In terms of content, three movies are discussed: Funny Games (1997), The Piano Teacher (2001) and Amour (2012).The selection of films was made on the basis of diversed musical plot devices used there. Additionally, these films show how role of music evolve over the years into more profound view inside events horizon, full-bodied commentary to film’s action and liberation from optical invigilation of camera.The goal of this paper is to show why narrative resource has crucial impact on artistic weight of Haneke’s films. The director renounces interpretation of his films by giving them their own life − the life of the open work. The article rises the argument that music supports the strategy of director. Moreover, it indicates that emancipation of the music entails the emancipation of heroes and diegetic reality.